Three-dimensional characterization of stress corrosion cracks - Lozano-Perez, S; Rodrigo, P; Gontard, L (2011)
Understanding crack propagation and initiation is fundamental if stress corrosion cracking (SCC) mechanisms are to be understood. However, cracking is a three-dimensional (3D) phenomenon and most characterization techniques are restricted to two-dimensional (2D) observations. In order to overcome this problem, different approaches to extract 3D information have been used in the recent years. In this work we will present the benefits of using 3D focused ion beam (FIB) slicing and electron tomography. 3D FIB slicing offers a fast and high throughput characterization while electron tomography offers the best spatial resolution. To illustrate the power of these techniques, different parts of dominant stress corrosion cracks in Ni-alloys and stainless steels have been reconstructed in 3D. All relevant microstructural features can now be studied in detail and its relative orientation respect to the strain direction and grain boundary plane accurately measured. © 2010 Published by Elsevier B.V. All rights reserved.